The role of digital platforms in promoting pro-sustainable behavior and conscious consumption by brands - Miguel, A.; Miranda, S. (Ecocycles, 2023)
The growing concerns about the effects of the climate crisis and the highest consumer expectations regarding the environmental performance of businesses led companies to adopt a greater sense of accountability for sustainability, and some of them even became advocators of environmental causes. Today, brands are increasingly using digital media to disseminate environmental brand activist campaigns, take a stand on ecological issues, and promote pro-environmental behaviors and conscious consumption practices, although not all brands succeed in this approach. This advanced review aims to address how brands are using online platforms, such as social networks and websites, to amplify their audiences' perceptions about environmental problems, inspire eco-friendly behaviors, and motivate conscious consumption. Thus, this article contributes to a better understanding of how digital media can be an opportunity, if well used, for brands to encourage positive environmental changes, giving current examples of environmental brand campaigns and discussing directions for future research in this field.